2016
DOI: 10.1016/j.jphs.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of choline transporter in tongue cancer: A novel molecular target for tongue cancer therapy

Abstract: We examined the functional characteristics of choline uptake in human tongue carcinoma using the cell line HSC-3. Furthermore, we explored the possible correlation between the inhibition of choline uptake and apoptotic cell death. Both choline transporter-like protein 1 (CTL1) and CTL2 mRNAs and proteins were expressed, and were located in plasma membrane and mitochondria, respectively. Choline uptake was saturable and mediated by a single transport system, which is pH-dependent. Several cationic drugs inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 27 publications
0
55
0
Order By: Relevance
“…Similar to the high-affinity choline transporter CHT1, CTL1 is selectively inhibited by the choline analogue hemicholinium-3 (CH-3), yet with a much lower sensitivity. In recent years, further choline uptake studies confirmed the expression and choline transporter function of CTL1/SLC44A1 in human lung alveolar cells, 28 mouse bone marrow-derived macrophages, 42 rat renal tubule epithelial cells, 30 human keratinocytes, 31 human brain microvascular endothelial cells, 14 rheumatoid arthritis synovial fibroblasts, 40 mouse muscle and liver cell lines, 32,33 and numerous cancer cell lines 26,28,[34][35][36][37][38][39]41 as summarized in Table 1.…”
Section: Slc44a Proteinsmentioning
confidence: 78%
See 2 more Smart Citations
“…Similar to the high-affinity choline transporter CHT1, CTL1 is selectively inhibited by the choline analogue hemicholinium-3 (CH-3), yet with a much lower sensitivity. In recent years, further choline uptake studies confirmed the expression and choline transporter function of CTL1/SLC44A1 in human lung alveolar cells, 28 mouse bone marrow-derived macrophages, 42 rat renal tubule epithelial cells, 30 human keratinocytes, 31 human brain microvascular endothelial cells, 14 rheumatoid arthritis synovial fibroblasts, 40 mouse muscle and liver cell lines, 32,33 and numerous cancer cell lines 26,28,[34][35][36][37][38][39]41 as summarized in Table 1.…”
Section: Slc44a Proteinsmentioning
confidence: 78%
“…In choline-deficient skin fibroblast from the postural orthostatic tachycardia syndrome (POTS) patient mentioned above, CTL1/SLC44A1 protein is reduced, and at the same time, oxygen consumption, mitochondrial potential, and glycolytic activity are diminished and mitochondrial function therefore impaired. 43 Recent studies could also localize CTL2/SLC44A2 protein to the mitochondria of human esophageal cells, 41 renal tubule epithelial cells, 30 human tongue carcinoma cells, 39 and human brain microvascular epithelial cells. 14 The purpose of a widely expressed choline transporter in the mitochondrial membrane is not clear yet, but it is likely that there is a link between CTL1/SLC44A1-mediated choline transport and mitochondrial phospholipid metabolism.…”
Section: Mitochondrial Choline Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…PMA and 4α-phorbol 12-myristate 13-acetate (4α-PMa) were acquired from wako Pure chemical industries, ltd., and hemicholinium-3 (Hc-3) was obtained from Sigma-aldrich, Merck Kgaa. we assessed the properties of [methyl-3 H]choline chloride uptake according to a previous study (13). radioactivity was measured using a liquid scintillation counter (Tri-carb ® 2100Tr, Packard) and [methyl-3 H]choline specific uptake was calculated as the difference between total [methyl-3 H]choline uptake in the presence and absence of 30 mM of unlabeled choline.…”
Section: Methodsmentioning
confidence: 99%
“…anti-β-actin pab-HrP-direcT antibody (PM053-7) was obtained from MBL. Fa2N-4 cell culture was performed according to a previously published procedure (13). in brief, membranes were incubated with rabbit anti-cTl1 polyclonal (ab110767) and anti-cTl2 monoclonal (clone 3d11) antibodies.…”
Section: Methodsmentioning
confidence: 99%